Characterization of the Paracoccidioides Hypoxia Response Reveals New Insights into Pathogenesis Mechanisms of This Important Human Pathogenic Fungus. - Patrícia de Sousa Lima; Dawoon Chung; Alexandre Melo Bailão; Robert A Cramer; Célia Maria de Almeida Soares (Public Library of Science (PLoS), 2015)
Hypoxic microenvironments are generated during fungal infection. It has been described that to survive in the human host, fungi must also tolerate and overcome in vivo microenvironmental stress conditions including low oxygen tension; however nothing is known how Paracoccidioides species respond to hypoxia. The genus Paracoccidioides comprises human thermal dimorphic fungi and are causative agents of paracoccidioidomycosis (PCM), an important mycosis in Latin America.In this work, a detailed hypoxia characterization was performed in Paracoccidioides. Using NanoUPLC-MSE proteomic approach, we obtained a total of 288 proteins differentially regulated in 12 and 24 h of hypoxia, providing a global view of metabolic changes during this stress. In addition, a functional characterization of the homologue to the most important molecule involved in hypoxia responses in other fungi, the SREBP (sterol regulatory element binding protein) was performed. We observed that Paracoccidioides species have a functional homologue of SREBP, named here as SrbA, detected by using a heterologous genetic approach in the srbA null mutant in Aspergillus fumigatus. Paracoccidioides srbA (PbsrbA), in addition to involvement in hypoxia, is probable involved in iron adaptation and azole drug resistance responses.In this study, the hypoxia was characterized in Paracoccidioides. The first results can be important for a better understanding of the fungal adaptation to the host and improve the arsenal of molecules for the development of alternative treatment options in future, since molecules related to fungal adaptation to low oxygen levels are important to virulence and pathogenesis in human pathogenic fungi.